Efektivitas Kebijakan Penanggulangan Pra Bencana Banjir Badan Penanggulangan Bencana Daerah (BPBD) di Kecamatan Batang Lubu Sutam Kabupaten Padang Lawas - Toga Ariansyah Siregar; Simson Ginting (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
Policy effectiveness is a measure of whether or not the achievement of the goals of an organization achieves its goals. If an organization achieves its goals, it has run effectively. The research method used is descriptive research with a qualitative approach. Data collection is carried out by interview, observation, and documentation techniques. The data obtained were analyzed qualitatively with the approach to the theory of effectiveness proposed by Richard Steers, including goal achievement, integration and adaptation. This study aims to determine the effectiveness of policies and work programs that have been made by the government and BPBD itself, as well as to find out what actions are needed by the government in efforts to overcome flood disasters in Batang Lubu Sutam District, Padang Lawas Regency. The results of the study show that there is still a low understanding of the community and government officials in responding to natural climate conditions that are prone to disasters and lack of awareness of community disasters in watersheds, indiscriminate tree felling/narrowing of watersheds carried out by communities in the upper reaches of the river.